2013
DOI: 10.3892/or.2013.2867
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor and HER2/neu downregulate expression of apoptosis-inducing factor in non-small cell lung cancer

Abstract: Abstract. Our previous study showed that patients with advanced stages of non-small cell lung cancer (NSCLC) were frequently detected with upregulation of hepatocyte growth factor (HGF). In vitro, HGF reduced expression of apoptosis-inducing factor (AIF) and cisplatin sensitivity in NSCLC cells. The effect of HGF was via HGF receptor (c-MET) and the downstream effector, focal adhesion kinase (FAK). In this study, we determined the prognostic value of AIF in NSCLC patients. AIF expression was determined by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(86 reference statements)
1
9
0
Order By: Relevance
“…Also, two previous reports showed that there was higher AIF expression in the majority of gastric carcinoma 60 and colorectal carcinoma 61. The similar phenomena could also been found in our colorectal carcinoma cohort, although AIF expression was shown to be decreased in many other tumor types, contributing to their chemoresistance 2 62. Our unpublished data showed that hypoxia inhibits AIF expression, and low AIF expression mainly exists in hypoxic regions of cancer tissues, although most cancer tissues expressed higher AIF.…”
Section: Discussionsupporting
confidence: 89%
“…Also, two previous reports showed that there was higher AIF expression in the majority of gastric carcinoma 60 and colorectal carcinoma 61. The similar phenomena could also been found in our colorectal carcinoma cohort, although AIF expression was shown to be decreased in many other tumor types, contributing to their chemoresistance 2 62. Our unpublished data showed that hypoxia inhibits AIF expression, and low AIF expression mainly exists in hypoxic regions of cancer tissues, although most cancer tissues expressed higher AIF.…”
Section: Discussionsupporting
confidence: 89%
“…Vescular endothelial growth factor (VEGF) is a well known factor involved in cancer metastasis and growth, and inhibition of VEGF has been widely used in clinical cancer therapy [27]. For lung adenocarcinoma, inhibition of EGFR and c-Met signaling pathway are also therapeutic strategies [12,17,18]. We found that increase in matrix rigidity gradually upregulated the expression of c-Met (Fig.…”
Section: Integrin/fak-mediated Mechanotransduction Selectively Upregumentioning
confidence: 86%
“…Clinical research has revealed that the activation of signaling pathways by the epidermal growth factor receptor (EGFR) and hepatocyte growth factor (HGF) receptor (c-Met) is closely associated with the growth and metastasis of NSCLC, including pulmonary adenocarcinoma [12,17,18]. Therefore, the interaction between adenocarcinoma cells and extracellular matrices with different matrix rigidities is critical for identifying the underlying mechanism of poor prognosis in patients with pulmonary adenocarcinoma and lung fibrosis.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that expression level of AIF inversely correlated with the expression of positive NSCLC markers, such as dihydrodiol dehydrogenase (DDH), MET, short oncostatin M receptor (OSMR), matrix metalloproteinase (MMP)-1, and HER2/neu, which were closely associated with drug resistance, tumor recurrence, metastasis, and poor prognosis. Addition of HGF inhibited AIF expression level in HER2/neu-silenced cells, indicating that both HGF and HER2/neu affect drug resistance by regulating AIF expression level in NSCLC [105]. …”
Section: Treatment Strategies: Monotherapy and Drug Combinationmentioning
confidence: 99%